Susceptibility testing of vancomycin, daptomycin and linezolid against methicillin-resistant Staphylococcus aureus - Wongsuk, Thanwa; Nutalai, Daranee (Journal of Medicine and Health Sciences, 2015)
Methicillin-resistant Staphylococcus aureus (MRSA) has been recognized as a major cause of healthcare-associated and community-acquired infections. The resistant genes of MRSA can be transferred very quickly between different strains. This study aimed to determine in vitro antimicrobial susceptibility and the minimal inhibitory concentration (MIC) of vancomycin, daptomycin and linezolid against methicillin-resistant Staphylococcus aureus (MRSA) from various clinical specimens of in- and out-patients and to study the antimicrobial susceptibility patterns. A total of 330 isolates of MRSA (in-patients = 295 isolates and out-patients = 35 isolates) from clinical specimens were obtained from Microbiology Laboratory, Faculty of Medicine, Vajira Hospital during April 2013 to March 2014. MIC of vancomycin and linezolid were performed by agar dilution technique and daptomycin by agar gradient diffusion technique. All of isolates were susceptible to vancomycin, daptomycin and linezolid. These results indicated that vancomycin, daptomycin and linezolid showed good activity against 330 MRSA tested (100% susceptibility). Therefore, they may be the drug of choices for MRSA treatment. การทดสอบความไวสารต้านจุลชีพ vancomycin, daptomycin และ linezolid ของเชื้อ methicillinresistant Staphylococcus aureus Methicillin-resistant Staphylococcus aureus (MRSA) เป็นสาเหตุสำคัญของโรคติดเชื้อในโรงพยาบาลรวมถึง เป็นสาเหตุของโรคติดเชื้อในชุมชน เชื้อสามารถส่งต่อยีนดื้อยาจากสายพันธุ์หนึ่งสู่อีกสายพันธุ์หนึ่งได้และสามารถแพร่ กระจายเชื้อดื้อยาได้อย่างรวดเร็ว การวิจัยนี้มีวัตถุประสงค์เพื่อทดสอบความไวและค่าความเข้มข้นของยา vancomycin, daptomycin และ linezolid น้อยที่สุดที่สามารถยับยั้งการเจริญของเชื้อ (MIC) ต่อเชื้อ MRSA จากสิ่งส่งตรวจของผู้ป่วย ภายในและผู้ป่วยนอกชนิดต่างๆ และศึกษาแบบแผนความไวต่อสารต้านจุลชีพ โดยเชื้อ MRSA 330 สายพันธุ์ (ผู้ป่วยใน จำนวน 295 สายพันธุ์และผู้ป่วยนอก จำนวน 35 สายพันธุ์) ที่ส่งมายังห้องปฏิบัติการจุลชีววิทยา คณะแพทยศาสตร์ วชิรพยาบาล ตั้งแต่เดือน เมษายน 2556 ถึงเดือน มีนาคม 2557 ทดสอบความไวของเชื้อ MRSA ต่อยา vancomycin และ linezolid ด้วยวิธีagar dilution technique และ daptomycin ด้วยวิธีagar gradient diffusion technique เพื่อหาค่า MIC พบว่า เชื้อ MSRA ร้อยละ 100, 99.09, 94.24 ไวต่อยา teicoplanin, fusidic acid และ trimethoprimsulfamethoxazole ตามลำดับ ประมาณร้อยละ 66.06 ยังคงไวต่อยา fosfomycin และร้อยละ 25.76 ไวต่อยา gentamicin ตามลำดับ โดยตัวอย่างเชื้อ MRSA ทั้งหมดไวต่อยา vancomycin, daptomycin และ linezolid ร้อยละ 100 บ่งชี้ว่ายาดังกล่าวมีประสิทธิผลที่ดีต่อการยับยั้งเชื้อ MRSA ในหลอดทดลอง โดยผลการทดสอบในห้องปฏิบัติการนี้สามารถ นำไปใช้เป็นแนวทางประกอบการพิจารณาเลือกใช้ยาเพื่อรักษาผู้ป่วยที่มีการติดเชื้อ MRSA